THE IMPACT OF THE LEGISLATION OF THE FIRST HALF OF THE 20TH CENTURY ON THE MODERN REGULATION OF THE RIGHTS AND DUTIES OF SWORN TRANSLATORS IN POLAND - ЛИТВИН, Катажина; КУЗЬМИНА, Екатерина (Comparative Legilinguistics, 2012)
The accession of Poland to the European Union in 2004 contributed to the development of a new, modern status of sworn translators, according to the European legal standards. The history of regulations concerning the profession of sworn translator in the Republic of Poland dates back to the first half of the 20th century. The rights and duties of translators set out in the primary legal acts, have been repeated (with relevant adjustments to the language and legal realities) over the following decades up to the present day. The authors analyze the historical legal acts enacted between 1920 and 1930 which regulated the procedures to be abided by sworn translators in Poland. The main focus of this paper is on the development of relevant regulations and their impact on both the present Ordinance on remuneration of sworn translators and the Polish Sworn Translation Act.